2022
DOI: 10.1002/cncr.34557
|View full text |Cite
|
Sign up to set email alerts
|

Perception of prognosis, quality of life, and distress in patients receiving chimeric antigen receptor T‐cell therapy

Abstract: Background Chimeric antigen receptor (CAR) T‐cell is potentially curative therapy for patients with hematologic malignancies but can cause life‐threatening toxicities. Data on perceptions of prognosis and psychological distress are lacking. Methods The authors conducted a cross‐sectional study of patients receiving CAR‐T. Before hospitalization for CAR‐T, patients completed assessments of quality of life (QOL) (Functional Assessment of Cancer Therapy‐General), anxiety and depression symptoms (Hospital Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…We observed an improvement in anxiety symptoms, even at the time of hospitalization, perhaps due to optimism about the expected efficacy of CAR T cells. 40 Change was statistically and clinically relevant from Months 3 to 12. The proportion of patients with depressive symptoms decreased over time, but change was not clinically relevant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We observed an improvement in anxiety symptoms, even at the time of hospitalization, perhaps due to optimism about the expected efficacy of CAR T cells. 40 Change was statistically and clinically relevant from Months 3 to 12. The proportion of patients with depressive symptoms decreased over time, but change was not clinically relevant.…”
Section: Discussionmentioning
confidence: 90%
“…In other studies, the prevalence of anxiety and depressive disorders at baseline are similar, ranging from 29% to 48% for anxiety and from 11% to 30% for depression. 8 , 40 , 41 Two studies found the prevalence of PTSD symptoms at baseline in 29% of patients before CAR T‐cell infusion. 6 , 40 Johnson and colleagues found a decrease in psychological distress over time, with 22% of patients experiencing anxiety and PTSD at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research studies have revealed a significant burden of psychologic distress among CAR-T cell recipients, including frequent symptoms of anxiety, depression, and post-traumatic stress disorder. 41,44,[104][105][106] Patients undergoing CAR-T cell therapy may experience a sense of loss, isolation, and frustration during repeated cycles of treatment and relapse, along with fear of recurrence and difficulty planning for the future in face of the uncertain prognosis following CAR-T cell therapy. 107 Additional challenges include the financial burden associated with treatment as well as the geographic, socioeconomic, and racial barriers to accessing CAR-T cell therapy.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…13 Unfortunately, most patients will ultimately experience disease progression and die of their illness, 13,14 and prior studies have demonstrated high rates of psychological distress in CAR T-cell therapy recipients. 15 Given the complexities and toxicities of CAR T-cell therapy, it is essential for clinicians to adequately educate patients about the risks and benefits.…”
Section: Introductionmentioning
confidence: 99%